Can a Rule-Based Expert System Diagnose Nasal Obstruction from Nasoendoscopy Videos? - Navaratnam, Annakan; Phoommanee, Nonpawith; Acharya, Vikas; Pendolino, Alfonso Luca; Leung, Terence S.; Andrews, Peter J. (Facial Plastic Surgery, 2025)
Nasal obstruction has multiple causes requiring specialist endoscopy for diagnosis. A rule-based expert system (RB-ES), which applies five “if–then” rules based on nasal features, may help replicate ENT decision-making in settings with limited access.This study evaluated RB-ES in diagnosing allergic rhinitis, chronic rhinosinusitis with (CRSwNP) and without (CRSsNP) nasal polyps, and deviated nasal septum. Primary outcomes were sensitivity and specificity; the secondary outcome was agreement with ENT specialists.Prospective cohort study.Seventy-one participants (65 patients, 6 controls) underwent pre- and postdecongestion endoscopy. Four ENT specialists provided diagnoses. RB-ES performance was compared against confirmed clinical diagnoses.RB-ES showed no detectable significant sensitivity differences from ENT specialists (all p > 0.05). Sensitivity was highest for CRSwNP; specificity remained high overall.RB-ES matched specialist performance in CRSwNP diagnosis. Dataset expansion and artificial intelligence integration are recommended for further validation.II.
Keywords: nasal obstruction; nasal endoscopy; rule-based expert systems